Geographical analysis of summer houses by the lake hazar in terms of their location of construction (Province of Elaziğ-Turkey) - Çağliyan, Ayşe; Ayhan, Gülsen (Editura Universitatii din Oradea, 2018)
The factors related to the location of the second houses are commonly related to geography and tourism geography. The second houses diversify according to time and place in terms of their location of construction and the distribution of these houses varies according to the physical and human geography elements. The discipline of geography has an important place in the identification of these elements and in the analysis of the location of the second houses. The aim of our study is to evaluate the summer houses situated in and around Lake Hazar in terms of their location and analyze their suitability in the sense of sustainability. Suitability of the summer houses were obtained with the help of Geographic Information Systems, the maps by using the “Multi-Criteria Decision Making” method and land use suitability classes by using “weighted overlay” and summer houses were classified as not suitable, moderately suitable and suitable. According to the suitability map and the field studies, since it lacked faulted steep slopes, the excess of the alluvial cone, and the presence of wide shores and beaches, the northern shores of the lake was more suitable for settlement and construction of the southern coast in comparison to the southern coats. These suitable locations were the Güney Village of the town of Sivrice, and Cevizdere and Gölardı Villages of the Central district. Some of the holiday sites-houses in the north of the lake were built along the stream and within the stream. Even though these areas were dry streams, they suffered from floods in the past and therefore, are not suitable for settlement. © 2018 Editura Universitatii din Oradea. All rights reserved.
Keywords: Elazig; Lake Hazar; Secondary Homes; Suitability Analysis; Tourism; Turkey